Inhibitor efficiency of migratory corrosion inhibitors to reduce corrosion in reinforced concrete exposed to high chloride environment. (11th October 2021) - Goyal, Arpit; Ganjian, Eshmaiel; Pouya, Homayoon Sadeghi; Tyrer, Mark
Highlights: Inhibitor efficiency of three different forms of migratory corrosion inhibitors were investigated for reinforced concrete. Electrochemical and permeability properties of inhibitors were studied. Organo-functional based inhibitors showed most efficient inhibitor efficiency and barrier properties. Abstract: Chloride-induced corrosion of steel reinforcement is the most important cause of premature failure of reinforced concrete structures. Corrosion inhibitors have proven to be an effective method to reduce corrosion rate in terms of application and cost-effectiveness. Various types of inhibitors are present such as organo-functional silanes, Amino-alcohol and Surfactant & amine salts-based inhibitors. The inhibitor efficiency of six major commercial migratory corrosion inhibitors, for reinforced concrete available in UK, was investigated using electrochemical study and permeability measurements to determine the most efficient inhibitor to protect steel in concrete with high chloride environment. It is showed that these compounds are effective inhibitors for reinforced concrete structures. Out of the tested inhibitors, organo-functional based inhibitors showed the best inhibitor efficiency and barrier properties.